2001
DOI: 10.2307/3236905
|View full text |Cite
|
Sign up to set email alerts
|

Forest plant communities of the Baohua Mountains, eastern China

Abstract: In the forest of the Baohua Reserve in the Baohua Mountains, eastern China, six plant communities and 11 subcommunities were described using the Braun-Blanquet method. These communities can be assigned to four already described Chinese vegetation types. Curtis' Compositional Index (CI) and Shannon's diversity index were used to determine the successional stage and species diversity of the communities. The community of Brachystachyum densiflorum and Pinus massoniana and the subcommunity of Fraxinus chinensis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…The successional patterns in the subtropical Ailao Mountains are based on previous studies by Wang [1983], Sheng and Xie [1990], and Young et al [1992], as well as on observed forest structure, peat depth, and gross peat stratigraphy. The successional patterns shown here, to about 500 years, are consistent with successions described from other subtropical forests of China [ Ming , 1987; Zhou et al , 1999; Chau and Marafa , 1999; An et al , 2001]. Wang [1983] further proposes that, in this region, succession occurs from peatland to Populus forest, although no data in support of this pathway are presented.…”
Section: Results and Interpretationsupporting
confidence: 85%
See 1 more Smart Citation
“…The successional patterns in the subtropical Ailao Mountains are based on previous studies by Wang [1983], Sheng and Xie [1990], and Young et al [1992], as well as on observed forest structure, peat depth, and gross peat stratigraphy. The successional patterns shown here, to about 500 years, are consistent with successions described from other subtropical forests of China [ Ming , 1987; Zhou et al , 1999; Chau and Marafa , 1999; An et al , 2001]. Wang [1983] further proposes that, in this region, succession occurs from peatland to Populus forest, although no data in support of this pathway are presented.…”
Section: Results and Interpretationsupporting
confidence: 85%
“…[16] The successional patterns in the subtropical Ailao Mountains are based on previous studies by Wang [1983], Sheng and Xie [1990], and Young et al [1992], as well as on [Ming, 1987;Zhou et al, 1999;Chau and Marafa, 1999;An et al, 2001]. Wang [1983] further proposes that, in this region, succession occurs from peatland to Populus forest, although no data in support of this pathway are presented.…”
Section: Successional Relationships Of Vegetation Typessupporting
confidence: 87%
“…sclerophylla is another important evergreen and shadetolerant tree species. It is widely distributed across subtropical areas of China from 200 to 1000 m above sea level, and it is one of the dominant and native species in evergreen broadleaved forests (An et al 2001). C. sclerophylla plays a significant role in water and soil conservation (Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%